(untitled) (Research, Society and Development, 2019)
Health organizations have estimated a high prevalence of hearing loss related to indiscriminate use of the individual sound device through earphones, and the user population seems to remain indifferent. It is intended to characterize the use of the individual sound device in young adults and to evaluate its effects on health, comparing audiological assessments with those of non-users of the device; and, to elaborate graphic material for the accomplishment of individual educational action of awareness and preventive approach. Were evaluated 72 subjects (48 device users and 24 non-users), male and female, with a mean age of 21.9 years. Anamnesis, otoacoustic emissions and high frequency audiometry were performed. For inferential statistical analysis were used the Mann-Whitney U test, Chi-square and Kruskal-Wallis. The use of the device predominated in conditions considered at risk and associated with auditory and extra-auditory complaints. There was no difference between the high frequency hearing thresholds, but they were lowered in the study group. There were more absent otoacoustic emissions in the study group and these differed by at least one frequency per ear, with the signal-to-noise ratios mostly lowered. Compared to the reported sound intensity and differences were observed mainly in relation to the control group. Finally, an individual educational action of awareness took place with the support of graphic material designed for this purpose. The study revealed evidence of early auditory change in the group of the device users compared to non-users, reinforcing a possible deleterious action of inappropriate use of the device. To this end, took place an individual awareness action that allowed the exchange of knowledge and reflection on hearing health.